COMMUNICATING INVASION: UNDERSTANDING SOCIAL ANXIETIES AROUND MOBILE SPECIES. Issue 2 (June 2015) - Ernwein, Marion; Fall, Juliet J.
ABSTRACT This article explores how discourses of threat concerning invasive alien species emerge and how ordinary citizens understand, receive and appropriate them. It explores the ambivalence of scientists and policy‐makers using emotive or highly charged terms and vocabulary, arguing that many make strategic yet cautious use of fear to raise awareness. Based both on in‐depth interviews of scientists and/or expert policy‐makers involved in communicating with the public about invasive species, as well as citizen focus groups, it further discusses how individuals reflect critically on the terms used in written documents. We argue that the various scientific uncertainties concerning the impacts of invasive species foster and feed other domains of social anxiety beyond the usual concern previous research has shown for xenophobic connotations. These include wider fears about environmental technology, science and expertise, changing environments, and threats to human health.